TINDAK TUTUR DIREKTIF ANAK AUTIS - Sumarti, Endang; Salamah, Umi (LITERA, 2015)
Abstract This study aims to describe forms, functions, and strategies in autistic children's directive speech acts. The data were from the recording of dialogs performed in an autism-specific school and an inclusive school in Malang City. They were collected through observations and recording. The data collection and analysis were interactively, simultaneously, and iteratively done to deeply and wholly understand forms, functions, and strategies in autistic children's directive speech acts. The results of the study are as follows. First, the forms include requests, commands, and prohibitions. Second, the functions comprise those of requesting, commanding, and prohibiting. Third, the strategies consist of a direct strategy and an indirect strategy.